2012
DOI: 10.4028/www.scientific.net/amm.226-228.406
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Vibration Reduction Characteristics of Ladder Track Structure on Metro Viaduct under Measured Track Irregularities

Abstract: 3D FEM models of ladder track and rail-bearing platform track on metro viaduct were established to analyze the vibration reduction characteristics of ladder track structure. Based on track irregularities measured by track inspection car, time-history vertical accelerations of rail, sleeper, flange and beam bottom were solved to contrast the dynamic characteristics of the two track structure. Results show that the vibration level of rail and sleeper are higher on ladder track than on rail-bearing platform track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The vibration of LS track and the vehicle increased significantly because of the lower vertical support rigidity of LS track when compared with typical slab tracks and the lack of efficient suppression of the upward vibration displacement of the sleeper. 13,14 Rail corrugation, sleeper hanging, sleeper cracking, elastic parts aging, and fastener system damage have all been observed in practical applications, 15,16 and the resonance frequencies of four typical track structures were investigated in References; 17,18 and the results showed that different track structures have varied effects on the geometric features and growth rate of rail corrugation. As for sleeper damping tracks, the initiation and growth of rail corrugation are mainly related to train speed, sleeper support spacing, sleeper mass, and support stiffness, which all play a role in the initiation and growth of rail corrugation on sleeper damping tracks.…”
Section: Introductionmentioning
confidence: 99%
“…The vibration of LS track and the vehicle increased significantly because of the lower vertical support rigidity of LS track when compared with typical slab tracks and the lack of efficient suppression of the upward vibration displacement of the sleeper. 13,14 Rail corrugation, sleeper hanging, sleeper cracking, elastic parts aging, and fastener system damage have all been observed in practical applications, 15,16 and the resonance frequencies of four typical track structures were investigated in References; 17,18 and the results showed that different track structures have varied effects on the geometric features and growth rate of rail corrugation. As for sleeper damping tracks, the initiation and growth of rail corrugation are mainly related to train speed, sleeper support spacing, sleeper mass, and support stiffness, which all play a role in the initiation and growth of rail corrugation on sleeper damping tracks.…”
Section: Introductionmentioning
confidence: 99%